Kinerja Pegawai Dalam Penerapan Sistem Manajemen Kesehatan Dan Keselamatan Kerja (Smk3) Di Pln Rayon Panrita Lopi Bulukumba - Sarif, Nurul Akbar; Mappamiring, Mappamiring; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to find out the coordination between government agencies inhandle sanctions ticketed vehicles illegal parking  in the city of Makassar and find out factors supporters and obstacles  in the process of the activity. This study had 12 informants. This type of research used qualitative research with the type of phenomenology that emphasized subjectivity human life experience. Data collection techniques were   observation, interview and documentation. The results of this study showed that coordination between government agencies in handling sanctions ticketed vehicles illegal parking in  Makassar City in general had been quite good but was still implemented  not optimal, it was seen from the aspects of (1) Communication, (2) Awareness of the importance of coordination and (3) Participant competence. Supporting factors in the implementation of this position mutation was (a) Communication and (b) Cooperation between each element involved.